RENAL LITHIASIS - Rahman, S. Jamil-ur-; Mohammad, Gul; zeb, Aurang (Journal of Ayub Medical College Abbottabad, 1993)
ABSTRACT: Two hundred and fifty patients with Urinary Tract Calculi, who were operated upon were studied in the period between 1986 to 1989. The maximum patients presented between thirty-one and forty years of age. Male to female ratio was 4.6-8.1. One hundred and twelve patients had Renal and sixty patients had Ureteric Stones. Seventy-eight patients had stone in the bladder and Urethra. the commonest symptom was pain, haematuria alone was present in twelve patients and pyuria alone in six patients. Urinary tract infection was present in one hundred and eighty patients. The overall mortality rale was 1.6%. Only one patient had recurrence. Majority of the stones were calcium oxalate or calcium phosphate.